Genetic architecture and combining ability of agronomic and nutritional traits in bread wheat (Triticum aestivum L.): A half diallel analysis using Griffing and Hayman approaches - Vikas, Verma; Deepak, Saran; Yashowardhan, Singh; Vikrant, Khare (Plant Science Today, 2026)
Wheat plays a pivotal role in global food and nutritional security, supplying a significant proportion of calories, protein and essential micronutrients such as iron (Fe) and zinc (Zn). However, breeding efforts focused on yield enhancement have often compromised grain nutritional quality, exacerbating micronutrient deficiencies in populations reliant on wheat as a staple. This study aimed to dissect the genetic architecture of key agronomic and nutritional traits in bread wheat using a comprehensive diallel mating design, combining Griffing’s combining ability analysis, Hayman’s graphical approach and Vr-Wr regression. Significant general combining ability (GCA) and specific combining ability (SCA) effects indicated the involvement of both additive and non-additive gene actions across agronomic and nutritional traits. Traits such as total protein content (TPC), grain iron content (GFeC) and grain zinc content (GZnC) exhibited high heritability and predictability, supporting the feasibility of selection-based breeding. In contrast, yield-related traits like grain yield per plant (GYPP) and grains per spike (GPS) were predominantly governed by non-additive effects, favoring heterosis breeding. Graphical analysis further confirmed overdominance and epistasis for complex traits, while additive effects dominated micronutrient traits. Promising parental lines, including JW 1203, HI 1633 and HI 1634, along with superior hybrids such as WB02 × HI 1633, were identified for their potential in combined yield and nutritional improvement. These findings highlight the necessity of dual breeding strategies, integrating selection-based approaches for micronutrient enhancement with heterosis breeding for yield improvement, to achieve sustainable gains in wheat productivity and nutritional quality. The insights generated provide a robust genetic framework for advancing biofortification and climate-resilient wheat breeding programs.